Comparison of the application of marketing communication tools used by organic food producers in Slovakia and Austria - Jarossová, Malgorzata A.; Minďašová, Karina (Engineering Sciences And Technologies, 2015)
The aim of the article was to compare the application of marketing communication tools used by organic food producers in Slovakia and Austria. Additionally, we were interested in the opinions of producers about customers, the differences between organic markets in Slovakia and Austria, and the barriers and opportunities to improve marketing communication in the organic food market. The survey was conducted using a standardized questionnaire developed in the Slovak and German languages by the authors of the article. The study population included 172 registered entities that have acquired the status of organic food producers. The effective rate of return of the questionnaire reached 40%. Based on the findings, it can be concluded that the Slovak organic food producers should make greater use of marketing communication tools in their business and develop distribution channels, for example: selling products in vending machines, which are used for this purpose in Austria [...]
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2015, Nr 4 (19), s. 32-48
Keywords: organic foods; Slovakia; Austria; producers; marketing communication; żywność ekologiczna; Słowacja; producent; komunikacja marketingowa